SPE Eastern Regional Meeting 2013
DOI: 10.2118/165721-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Advances in Shale Reservoir Analysis Using Flowback Data

Abstract: Shale reservoirs with multistage hydraulic fractures are commonly characterized by analyzing long-term gas production data, but flowback data is usually not included in the analysis. However, this work shows there can be benefits to including flowback data in well analysis. The flowback period is dominated by water flow. Field data indicate that only 15-30% of the frac water is recovered after the flowback. Past publications have suggested that the lost water is trapped in the natural fracture or imbibed into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…After cracking a well, the fluid is removed from the drillbore as well as from the cracks and gaps in the surrounding rock. As has been proved in American research, the amount of the fluid obtained in shale gas fracturing is lower than in the case of a tight oilfield: 40-60% for a vertical well and 10-30% for a horizontal well [11,12].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…After cracking a well, the fluid is removed from the drillbore as well as from the cracks and gaps in the surrounding rock. As has been proved in American research, the amount of the fluid obtained in shale gas fracturing is lower than in the case of a tight oilfield: 40-60% for a vertical well and 10-30% for a horizontal well [11,12].…”
Section: Introductionmentioning
confidence: 81%
“…Total Petroleum Hydrocarbon (TPH) was analyzed by gas chromatography (GC) [11]. Chloride analyses were done with an argentometric method.…”
Section: Research Methodology and Materialsmentioning
confidence: 99%
“…Firoozabadi and Hauge (1990) have demonstrated that fracture capillary pressure is greater than zero, depending on the roughness, aperture, and pore structure. This is inconsistent with Cheng (2012), in which zero secondary fracture capillary pressure was used, and Wattenbarger and Alkouh (2013), in which the secondary fracture capillary pressure was the same as the matrix capillary pressure. In addition, wettability influence has often been ignored: assuming neural wettability and identical relative permeability functions in both matrix and secondary fractures (Wattenbarger and Alkouh, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…However, less than 50% of fracturing fluids are typically recovered (McClure, 2014;Cheng, 2012;Wattenbarger and Alkouh, 2013). Three fluid-loss mechanisms have been reported in the literature (Pagels et al, 2012;Wattenbarger and Alkouh, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation